PENGARUH INVERSI FILTER Q TERHADAP AMPLITUDO SESAAT (INSTANSTANEOUS AMPLITUDE) DATA SEISMIK: THE EFFECT OF FILTER Q INVERSION ON AMPLITUDE INSTANT (INSTANEOUS AMPLITUDE) SEISMIC DATA - Khristian Enggar Pamuji (Universitas Papua, 2015)
Seismic waves travelling through media are attenuated by the conversion of elastic energy into heat. Uponbeing attenuated, the travelling wave changes: amplitude is reduced, travelling waveform is modified due tohigh-frequency content absorption, and phase is delayed. In this study, the effect of attenuation on seismic datawas reduced by applying inverse Q filter method. Application of inverse Q filter on seismic data, can improve thequality and resolution of data. Improving the seismic data quality and its resolution can be seen at seismicattributes (Instantaneous Amplitude) of seismic data. The results of study indicate that the seismic attributes(instantaneous amplitude) would be better if the inverse Q filter was applied.